2004
DOI: 10.1002/jez.a.58
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and stress‐induced glucocorticoids during reproduction in the variable flying fox, Pteropus hypomelanus (Chiroptera: Pteropodidae)

Abstract: Baseline and stress-responsive glucocorticoid (GC) levels were assessed during early pregnancy, late pregnancy, and lactation in female variable flying foxes (Pteropus hypomelanus) and in males over the same time period. Animals were maintained in a breeding colony in captivity. High levels of both cortisol and corticosterone were detected, with total plasma GC levels being among the highest documented in vertebrates (up to 3000 ng/ml in individual animals, with cortisol being the primary GC, accounting for ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 27 publications
3
26
0
1
Order By: Relevance
“…Serial plasma samples collected over time from the same individuals (i.e., longitudinal sampling) have been particularly informative for clarifying relationships of GCs with a multitude of potentially important natural and anthropogenic stressors. Longitudinal sampling enables detailed study of cycles in GC secretion, relationships of GCs to long-lasting reproductive states such as pregnancy or lactation, and can help discriminate cases of chronic vs. acute stress events (e.g., Bettendorf et al, 1998;Grant et al, 2016;Koester et al, 2015;Reeder et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Serial plasma samples collected over time from the same individuals (i.e., longitudinal sampling) have been particularly informative for clarifying relationships of GCs with a multitude of potentially important natural and anthropogenic stressors. Longitudinal sampling enables detailed study of cycles in GC secretion, relationships of GCs to long-lasting reproductive states such as pregnancy or lactation, and can help discriminate cases of chronic vs. acute stress events (e.g., Bettendorf et al, 1998;Grant et al, 2016;Koester et al, 2015;Reeder et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A. jamaicensis shows a characteristic, sex-independent stress response with corticosterone levels rising from a baseline to a maximum followed by a subsequent decrease. Surprisingly, the corticosterone response in A. jamaicensis was less rapid than in M. lucifugus (significant 15 min after capture) and captive flying foxes, Pteropus hypomelanus (significant after 20 min of restraint; Widmaier and Kunz 1993;Reeder et al 2004b). Why is the corticosterone stress response in A. jamaicensis delayed compared to the other two species studied in subtropical and temperate settings?…”
Section: Discussionmentioning
confidence: 93%
“…In tropical bats, glucocorticoid levels are among the highest documented for mammals (Kwiecinski and Damassa 2000). However, most results so far stem predominantly from captive individuals (Widmaier and Kunz 1993;Widmaier et al 1994;Kwiecinski and Damassa 2000;Reeder et al 2004b) and data on free-ranging populations are largely lacking (but see Reeder et al 2004a). Extremely high GC levels may terminate pregnancies (Heideman 2000), triggering a life-protecting emergency life-history stage (Wingfield et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of Pteropus species have found that cortisol is the primary glucocorticoid occurring in plasma (Widmaier and Kunz 1993, Widmaier et al 1994, b Reeder et al 2004, and that animals exhibit significant elevations in plasma glucocorticoid levels in response to restraint stress. Widmaier et al (1994) concluded that bats possess a stress response similar in some ways to other mammals.…”
mentioning
confidence: 99%